The 2ómega-dimensional light-cone integrals with momentum shift - Suzuki, A. T. [UNESP] (American Institute of Physics (AIP), 1988)
A class of light-cone integrals typical to one-loop calculations in the two-component formalism is considered. For the particular cases considered, convergence is verified though the results cannot be expressed as a finite sum of elementary functions. © 1988 American Institute of Physics.